Measurement of SLC5A5 Gene Expression in Patients with Hypothyroidism - Hussein Abees Al-Yasari, Fatimah; Hasson Sukban, Liqaa (Pure Sciences International Journal of Kerbala, 2025)
This study determines the amount of gene expression level of the SLC5A5 gene in women with hypothyroidism (HD), as it is one of the key genes influencing the development of the condition. Additionally, some risk factors were examined, including diabetes, hypertension, heart diseases, prior thyroidectomy, and family genetic history, to assess the impact of these factors on the prevalence of HD. Peripheral blood (PB) samples were obtained from 50 women with HD who were followed up by medical diagnosis and whose ages ranged from (40 to 70) years. 50 samples of healthy women who do not suffer from chronic diseases were selected as a control group. Polymerase chain reaction (qPCR-RT) technique was used to quantify expression SLC5A5 gene levels in the samples, as well as to measure some hormonal criteria for patients with thyroid disease to demonstrate their importance in diagnosing the disease. The level of thyroid stimulating hormone (TSH) and the thyroid hormones thyroxine (T4) and triiodothyronine (T3) were measured. The results showed no statistically significant on the expression of the SLC5A5 gene in women with hypothyroidism compared with the healthy group. In contrast, the results of thyroid hormones showed a significant decrease in both triiodothyronine (T3) and thyroxine (T4) and non-significant effect of TSH. Additionally, the findings indicated that factors such as family history, diabetes, hypertension, and heart disease contribute to the development of HD. In conclusion, risk factors such as family history, diabetes, hypertension, and heart disease were found to play a role in the development of the condition, emphasizing the multifactorial nature of HD.